2014
DOI: 10.3390/molecules190710279
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Product Citral Can Cause Significant Damage to the Hyphal Cell Walls of Magnaporthe grisea

Abstract: Abstract:In order to find a natural alternative to the synthetic fungicides currently used against the devastating rice blast fungus, Magnaporthe grisea, this study explored the antifungal potential of citral and its mechanism of action. It was found that citral not only inhibited hyphal growth of M. grisea, but also caused a series of marked hyphal morphological and structural alterations. Specifically, citral was tested for antifungal activity against M. grisea in vitro and was found to significantly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Citral was able to inhibit conidia germination, suppress germ tube elongation, restrain mycelium growth, and prevent colony development in a concentration-dependent manner in vitro. After exposure to citral, the surface of mycelium cells observed under a scanning electron microscope (SEM) became wrinkled, the mycelium cell wall became thin, the cell membran was impaired, and the villus-like material outside the cell wall was lost (29). Sha et al studied the interactions between two B. subtilis strains SYX04 and SYX20 and M. oryzae.…”
Section: Discussionmentioning
confidence: 99%
“…Citral was able to inhibit conidia germination, suppress germ tube elongation, restrain mycelium growth, and prevent colony development in a concentration-dependent manner in vitro. After exposure to citral, the surface of mycelium cells observed under a scanning electron microscope (SEM) became wrinkled, the mycelium cell wall became thin, the cell membran was impaired, and the villus-like material outside the cell wall was lost (29). Sha et al studied the interactions between two B. subtilis strains SYX04 and SYX20 and M. oryzae.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al. () demonstrated that citral was capable of inhibiting mycelial growth, conidial formation and germination, appressorium formation and damaging the hypha cell walls of M. grisea . Tao, Jia, et al.…”
Section: Discussionmentioning
confidence: 99%
“…Each treatment contained four replicates and at least 100 spores per treatment were examined under the light microscope (Leica DM 3,000, Leica microsystem, Germany) at 40 × magnification after each exposure to the plant volatile and the number of germinated spores per replicate was determined. The germination and inhibition percentage was calculated as described by Li, Wu, Yin, Liang, and Li () using the formula: %normalSpore0.166667emnormalgermination=normalTotal0.166667emnormalnumber0.166667emnormalof0.166667emnormalgerminated0.166667emnormalspores×100Totalnumberofexaminedspores%Inhibition=(ScSt)normalSc×100where Sc is the average number of spore germinated in the control trials and St is the average number of spore germinated in the treated trials.…”
Section: Methodsmentioning
confidence: 99%
“…The disease can cause harm to rice throughout the year and can occur on various parts of the plant. Global annual rice yield losses caused by M. grisea range from 11 to 30% (Tang et al, 2013;Li et al, 2014;Zhu et al, 2014;Shanmugapackiam et al, 2015), and infection can even cause crop failure. Spores are mainly responsible for infection (Choi et al, 2013;Motallebi et al, 2013;Li et al, 2014;Nehls and Dietz, 2014;Babu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%